Comparative Analysis of Religious Moderation in Islamic and Western Perspectives - Baiti, Masnun; Rusli, Risan; Sukardi , Ismail; Dian Andesta Bujuri; Sukirman; Septia Fahiroh (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2026)
This article systematically examines the similarities and differences in the concept of religious moderation from Islamic and Western perspectives using a qualitative library research approach based on books, scholarly articles, research reports, and relevant academic journals. The comparative analysis highlights that both traditions reject extremism and violence while emphasizing tolerance and respect for diversity. In Islam, religious moderation is grounded in the principle of wasathiyah, which promotes balance, justice, tolerance, deliberation, and peace as integral values derived from the Qur’an and Sunnah. In contrast, Western religious moderation has evolved through long historical processes, including intra-church conflicts, the Reformation, the Enlightenment, and the development of moderate secularism, and is primarily based on rationality, democratic practices, pluralistic values, and the protection of human rights. Within the Indonesian context, these two perspectives are conceptually integrated through Pancasila, which serves as the philosophical foundation of social and state life, thereby reinforcing religious moderation as a shared framework for maintaining harmony in a pluralistic society